Nur Masalha, The Zionist Bible: Biblical Precedent, Colonialism and the Erasure of Memory : (BibleWorld; Durham: Acumen Publishing, 2013), vii + 295 pp. ISBN 978-1-84465-657-8 - Pfoh, Emanuel Oreste (2015)
The exposition of the political implications of biblical scholarship is nowadays not a novelty, especially since the publication in 1996 of K.W. Whitelam’s The Invention of Ancient Israel: The Silencing of Palestinian History. However, it is not usual to find a book making so direct and bold statements, yet argued and sustained by facts and bibliography, such as the present work under review. Nur Masalha is not a biblical researcher, but a scholar of the modern Israeli-Palestinian conflict. He has, however, managed to survey the current state of Old Testament historical studies and shows how the biblical past that scholars attempt to reconstruct was used to support or legitimize contemporary political, economic, ideological and social conditions and realities in Israel/Palestine. In this sense, Masalha’s book aligns itself with the critical line of scholarship started by Whitelam: if Whitelam exposed how modern Western biblical scholarship was tainted by the ideological and political present, this book rather expands the argument on the reception and the impact of Western and especially Israeli biblical imagination on Palestinian lives throughout the twentieth century.